2018
DOI: 10.1183/20734735.000218
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in bronchiectasis: a real issue?

Abstract: Gender differences in chronic respiratory disease, including cystic fibrosis and non-cystic fibrosis bronchiectasis are clinically apparent and of increasing importance. Differences in disease prevalence, severity and outcome are all described, however, the precise cause of the gender dichotomy and their associated underlying mechanisms have been poorly characterised. A lack of dedicated clinical and epidemiological research focused in this area has led to a paucity of data and therefore a lack of understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 191 publications
2
49
0
1
Order By: Relevance
“…We show that the concentration and chemical nature of the steroid hormone shape the level of response together with the membrane properties of the exposed P. aeruginosa strain. This finding might explain sex differences observed across a range of lung diseases affected by chronic Pseudomonas infections ( 1 , 2 , 4 ). Females with CF have earlier colonization ( 8 , 49 51 ) and mucoid conversion of P. aeruginosa ( 8 , 52 ), which in turn, translates to poorer clinical outcomes and higher mortality ( 8 , 52 54 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We show that the concentration and chemical nature of the steroid hormone shape the level of response together with the membrane properties of the exposed P. aeruginosa strain. This finding might explain sex differences observed across a range of lung diseases affected by chronic Pseudomonas infections ( 1 , 2 , 4 ). Females with CF have earlier colonization ( 8 , 49 51 ) and mucoid conversion of P. aeruginosa ( 8 , 52 ), which in turn, translates to poorer clinical outcomes and higher mortality ( 8 , 52 54 ).…”
Section: Discussionmentioning
confidence: 82%
“…Clinical observations and research reveal that males are at higher risk for bacterial infection; however, females are more prone to develop more severe illness with poorer outcomes, particularly at reproductive age ( 1 3 ). Genetic, anatomical, social, and behavioral differences have all been advanced to explain these gender biases, however, more recently, variations in the host innate and adaptive immune responses under the control of sex steroid hormones have been proposed ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study with Chinese subjects with bronchiectasis, women walked significantly less than men 21 . Besides the prevalence of bronchiectasis is higher in males, the disease is more severe in females due to the differences in physical and biological mechanisms, such as smaller lungs, earlier bacterial colonization, nutritional deficiencies, estrogen/progesterone modulate cilia beat affecting the mucociliary escalator and delayed diagnosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and clinical evidence has demonstrated that of the 1 billion people world‐wide suffering from acute or chronic lung disease, a disproportionate number of these individuals are women (Forum of International Respiratory Societies & European Respiratory Society, ; Fuentes & Silveyra, ). Lung diseases that present with increased incidence and/or severity in women include: non and cigarette‐mediated chronic obstructive pulmonary disease (COPD, particularly the chronic bronchitis form), autoimmune lung disease, pulmonary hypertension (Pinkerton et al, ), bronchiectasis (non and cystic fibrosis‐related; Vidaillac, Yong, Jaggi, Soh, & Chotirmall, ), chronic respiratory symptoms due to air pollution from ozone and particulate matter (Fuentes, Roy, Mishra, Cabello, & Silveyra, ; Yoshizaki et al, ), and adult asthma (Carey, Card, Voltz, Arbes Jr, ). However, there are also a number of lung diseases that affect men disproportionately, such as lung cancer and pulmonary fibrosis (Fuentes et al, ; Sathish & Prakish, 2016).…”
Section: Introductionmentioning
confidence: 99%